GLI ESORDI E GLI SVILUPPI DELL’EMIGRAZIONE ITALIANA NELLA «VECCHIA SHANGHAI» - Stefano Piastra (Bollettino della Società Geografica Italiana)
After the First Opium War (1839-1842) and the Treaty of Nanjing (1842), Shanghai was opened to international trade, and experienced a period of cosmopolitism and economic growth as far as the Japanese occupation during WWII: the international urban environment of those years has been renamed ‘Old Shanghai’. Italians migrated to the ‘Old Shanghai’ in several phases, with different purposes. At first (1850s-1860s), some Italian traders, known as ‘semai’ (mainly from Piedmont and Lombardy), were involved in silkworm eggs trade, in the framework of the attempts to defeat the pébrine (a silkworms disease which threatened the silk sector in Europe) through the importation of pébrine-free silkworm eggs in the West. Even the institution, in these years, of a Consulate of the Kingdom of Sardinia in Shanghai (1860), later become Consulate of the Kingdom of Italy, was indirectly linked to Italian business in silkworm eggs and silk in the city. Later (1870s-1880s), Italian managers and supervisors of steam silk filatures, mainly from Milan area (where silk sector was very well developed and based on an industrial approach), moved to the ‘Old Shanghai’, serving for English-, American- or German-owned silk companies. At the dawn of the 20th century, several Lombard businessmen got enough know-how, funds and business reputation to open in Shanghai their own silk filatures or silk import/export companies. Italian community in the ‘Old Shanghai’ was small and in a minority report if compared with the international environment of the city: this is the reason why the recruitment of Italians (mainly, Lombards) as silk filature supervisors, employees or business partners was based on mutual trust, kinship or previous work experience as colleagues (in Lombardy or in Shanghai), more than CV or independent references.